Evaluation of the role of FMR1 CGG repeat allele in Parkinson’s disease from the Chinese population - Chen, Juan; Zhao, Yuwen; Zhou, Xun; Xue, Jin; Xiao, Qiao; Pan, Hongxu; Zhou, Xiaoxia; Xiang, Yaqin; Li, Jian; Zhu, Liping; Zhou, Zhou; Yang, Yang; et al. (Frontiers in Aging Neuroscience, 2023)
Objective There is controversial evidence that FMR1 premutation or “gray zone” (GZ) allele (small CGG expansion, 45–54 repeats) was associated with Parkinson’s disease (PD). We aimed to explore further the association between FMR1 CGG repeat expansions and PD in a large sample of Chinese origin. Methods We included a cohort of 2,362 PD patients and 1,072 controls from the Parkinson’s Disease and Movement Disorders Multicenter Database and Collaborative Network in China (PD-MDCNC) in this study and conducted repeat-primed polymerase chain reaction (RP-PCR) for the size of FMR1 CGG repeat expansions. Results Two PD patients were detected with FMR1 premutation (61 and 56 repeats), and the other eleven PD patients were detected with the GZ allele of FMR1 CGG repeat expansions. Those thirteen PD patients responded well to levodopa and were diagnosed with clinically established PD. Specifically, one female PD patient with GZ allele was also found with premature ovarian failure. However, compared to healthy controls, we found no significant enrichment of GZ allele carriers in PD patients or other subgroups of PD cases, including the subgroups of female, male, early-onset, and late-onset PD patients. Furthermore, we did not find any correlation between the FMR1 gene CGG repeat sizes and age at onset of PD. Conclusion It suggested that FMR1 premutation was related to PD, but the GZ allele of FMR1 CGG repeat expansions was not significantly enriched in PD cases of Chinese origin. Further larger multiple ethnic studies are needed to determine further the role of the FMR1 GZ allele in PD.